Distance to HIV and Antenatal Care: A Geospatial Analysis in Siaya County, Kenya. (September 2019) - Kohler, Pamela K.; Akullian, Adam; Okanda, John; Otieno, George; Kinuthia, John; Voss, Joachim; Zierler, Brenda; John-Stewart, Grace
Abstract: As maternal child health (MCH) programs expand in the setting of HIV, health systems are challenged to reach those most vulnerable and at the greatest need. Cross-sectional surveys of MCH clinics and recent mothers in the Siaya Health Demographic Surveillance System were conducted to assess correlates of accessing antenatal care and facility delivery. Of 376 recent mothers, 93.4% accessed antenatal care and 41.2% accessed facility delivery. Per-kilometer distance between maternal residence and the nearest facility offering delivery services was associated with 7% decreased probability of uptake of facility delivery. Compared with a reference of less than 1 km between home and clinic, a distance of more than 3 km to the nearest facility was associated with 25% decreased probability of uptake of facility delivery. Distance to care was a factor in accessing facility delivery services. Decentralization or transportation considerations may be useful to optimize MCH and HIV service impact in high-prevalence regions.